Nitrogen and Phosphorus Exchanges Across the Sediment–Water Interface in a Bay of Lake Chaohu: Liu et al. (1st November 2018) - Liu, Cheng; Gu, Xiaozhi; Chen, Kaining; Fan, Chengxin; Zhang, Lei; Huang, Wei
ABSTRACT: : A year‐long field investigation was carried out in the most heavily polluted bay of Lake Chaohu to assess the temporal exchanges of ammonium nitrogen ( ) and soluble reactive phosphorus (SRP) across the sediment–water interface (SWI) and to provide remediation advises. Results showed that the monthly average fluxes of and SRP were 31.38 and 6.98 mg m –2 d –1, respectively, both of which were higher than those in many other hyper‐eutrophic lakes around the world. The exchanges of and SRP were both closed related to the oxygen penetration. Low oxygen penetration depth and generally negative oxygen uptake rates provoked the dissolution of redox sensitive phosphorus and labile in the sediment and increased the fluxes. In addition, the generally higher fluxes during late spring to autumn should be noted during the reduction of internal loadings, when applicable techniques should be implemented accordingly to achieve better reduction effects.